Improve the audit process of loans in financial audit at Deloitte VietNam - Nguyen, Thi Nga (H. : ĐHQGHN, 2020)
The thesis provided theoretical framework for auditing loan accounts in the financial statement and analyze the methodology applied in Deloitte Vietnam Ltd to perform audit for loan section. Based on that, the thesis pointed out some strengths, weaknesses, as well as give reasonable solutions, recommendations to improve the process of auditing the loan section performed by Deloitte Vietnam Ltd.